A Review of Ethnomedicinal Plant Resources in Southern Nigeria - Enebeli-Ekwutoziam, Katherine Chinwe; Aruah, Chinenye Blessing; Ogbonna, Blessing O.; Eze, Uju Judith; Egedeye-Fubura, Fabaraye Sokari; Nwankwo, Chigozie F.; Oliseyenum, Ifeoma N.; Udoha, Ngozi Winfred; Afuye, Tubosun Nathaniel; Asogwa, Grace N.; Chinweokwu, Kris Ada; Anenih, Farida O.; et al. (Ethnobotany Research and Applications, 2021)
Background: The inadequate programs established to eradicate numerous health problems in Nigeria have led to little improvement in the health status, especially in southern Nigeria. Southern Nigeria has a high prevalence rate of malaria, typhoid, fevers, colds and chills, catarrh, flu, river blindness, respiratory disorders, eye problems and skin infections. The strain caused by the dire need to provide a financial health coverage for the family, a poorly developed health care systems and functional surveillance has led to the exploration of alternative medicine by the indigenes of southern Nigeria.This study aims at documenting information on the common plant resources employed in the ethnomedicinal practices of the indigenous people of the Southern Nigeria, and to explore ways of sensitizing genuine conservation efforts in the face of threat of genetic erosion posed to these resources due to anthropogenic activities. Materials and methods: Onsite ethnomedicinal survey in the study area was carried out between September 2019 and November 2020 to document an indigenous medicinal plant traditional knowledge. Interviews were conducted with the aid of a local language interpreter. Data were obtained using 300 semi-structured questionnaires. Consultations were made on all available information about traditional medicinal plants and ethnomedicinal surveys in Southern Nigeria. Online electronic databases including Google scholar, Research Gate, SciFinder, ScienceDirect and Open Thesis were used to search for relevant literature. Ethnomedicinal data were analyzed using the Relative frequency of citation (RFC), Fidelity level (FL), Relative popularity level (RPL), Use value (UV) and Informant Consensus Factor (ICF). Results: A total of 236 species belonging to 80 families were reported by this study. Fabaceae was the most represented family having thirty (30) plant species. The three (3) regions had varying frequencies of occurring plants species. South-Western Nigeria represented the region with the highest plant occurrence (47%) followed by South–South (31%). Leaves (42.32%) were the most common parts used in the preparation of herbal remedies. Decoctions (48.89%) were the most common method of plant preparation used in herbal remedies. Regional distribution and occurrence of ethnomedicinal plant resources of Southern Nigeria is reported here for the ﬁrst time. Conclusion: Medicinal plants play crucial role in the treatment of various ailments by the indigenous people in Southern Nigeria. This study highlights the level of species richness as well as biodiversity in the study area. Bioactivity and toxicity by in vitro and in vivo standard tests should be made on herbal drug extracts of the presented species for isolation and possible identiﬁcation of potentially active compounds